Photoeletrolytic system applied to remazol red brilliant degradation - Sousa, Mariana Lopes [UNESP]; Moraes, Peterson Bueno; Bidoia, Ederio Dino [UNESP] (I W A Publishing, 2011)
Toxicity tests using Sacharomycces cerevisiae were made with simulated textile effluents containing reactive dye (remazol red brilliant) treated by photoeletrolytic process, varying treatment time and applied current. The treatment incorporated an electrolytic reactor with rectangular titanium anode coated with 70% TiO(2)/30% RuO(2) cathode and a rectangular stainless steel coupled with another photolytic reactor containing a high power UV lamp. The treatment system was used in batch recirculation, in other words, the simulated effluent was driven by the system through a helical pump. It was observed that the higher the value of current applied, the longer the treatment has greater color removal of textile effluent and higher mortality of S. cerevisiae, killing up to 100% of the cells at the end of the treatment. With a lower current applied and having the treatment time of 5 minutes, the effluent showed a color removal of 97% and a lower mortality of S. cerevisiae than the effluent simulated without any treatment.
Keywords: remazol red brilliant; Saccharomyces cerevisiae; photoeletrolytic treatment; toxicity; textile effluent